Goat Farming Business in Communal Enclosure Through Female Farmer Empowerment - Irfina Widya stiqomah; Mohamad Harisudin (Journal of Global Innovations in Agricultural Sciences)
The integration of agriculture and livestock plays an important role in food security through the utilization of plant waste for animal feed and the processing of livestock manure into fertilizer. The livestock sector has great potential for development, supported by the continuously increasing demand for animal protein consumption. Women play a role in livestock management, but their competence is still low due to limited access to capital, training, and supporting infrastructure. This research aims to analyze in-depth the process of women's empowerment in livestock management through communal enclosure and its impact. The research method is qualitative with a case study approach. Data were collected through in-depth interviews, observations, and documentation. The research results show that livestock management with empowerment has economic and social impacts for women. The presence of communal system innovations in shared barn management, a goat kid redemption system, and a livestock manure exchange system in the form of water to address drought issues. The role of change agents, family support, and strong social capital are key factors in the success of empowerment. The strategy involves engaging supporting stakeholders to strengthen their roles by increasing motivation and participation. This study recommends the creation of specific policies to support the empowerment of women in sustainable farming practices. Keywords: CSR, communal enclosure, goat farming, female farmer group, empowerment, social capital, stakeholders.